PERENCANAAN JARINGAN EVOLUTION DATA OPTIMIZED (EVDO) PADA TELKOM FLEXI AREA JAKARTA - Henry Candra; Muhammad Ikhsan Fauzi (Website, 2013)
Abstract The development of high-speed data connection and internet in mobile phones technologies is rapidly growing lately. Certain technology that support the growth of mobile data communication is EVDO system. EVDO offers wireless internet technology for data optimization and internet access with high speed data rate and large capacity. This technology also provides a solution for wireless mobile internet with high performance. EVDO can achieve peak data rates up to 2.45 Mbps on the forward link with the use of 1.25 MHz wide spectrum. This paper discusses Network Evolution Data Optimized (EVDO) plan at Telkom Flexi Jakarta. The area of discussion includes traffic prediction, and coverage area to existing BTS CDMA 2000 1x. Based on the prediction, the number of customers in 2015 for the dense urban areas in Central Jakarta will be 150,000 customers, while in the urban area of West Jakarta will reach 60,000 customers and the local urban areas in North Jakarta will have 60,000 subscribers. The offered traffic in dense urban area North Jakarta is 15,170 Kbps/km2, while in urban area of West Jakarta is 17,455 Kbps/km2, and for the urban area in North Jakarta is 13,473 Kbps/km2. Keywords: EVDO, wireless network, internet access.